2001
DOI: 10.1054/bjoc.2000.1701
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal radiosensitivity as a marker of predisposition to common cancers?

Abstract: SummaryWe previously found that 40% of breast cancer patients showed enhanced sensitivity to X-ray induced chromosome damage in G 2 lymphocytes and suggested that this might indicate a low penetrance predisposition to breast cancer, for which there is good epidemiological evidence. We have now tested the hypothesis that elevated G 2 radiosensitivity is a marker of such predisposition to other common cancers. We tested patients with colorectal cancer, for which there is also good epidemiological evidence of inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
69
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 20 publications
6
69
0
Order By: Relevance
“…In breast cancer patients the elevated chromosomal radiosensitivity is confirmed in several independent studies (Scott et al, 1994(Scott et al, , 1998Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001a;Riches et al, 2001). In these studies the G2 assay, which involves the analysis of chromatid breaks in metaphase cells that are irradiated during the G2 phase of the cell cycle, was used to evaluate chromosomal radiosensitivity.…”
Section: Introductionmentioning
confidence: 93%
“…In breast cancer patients the elevated chromosomal radiosensitivity is confirmed in several independent studies (Scott et al, 1994(Scott et al, , 1998Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001a;Riches et al, 2001). In these studies the G2 assay, which involves the analysis of chromatid breaks in metaphase cells that are irradiated during the G2 phase of the cell cycle, was used to evaluate chromosomal radiosensitivity.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have shown that enhanced chromosomal radiosensitivity is also present in a significant proportion of cancer patients (Scott et al, 1994(Scott et al, , 1998Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001Baria et al, , 2002Buchholz and Wu, 2001;Papworth et al, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005Ban et al, 2004;Howe et al, 2005;Kolusayin Ozar and Orta, 2005;Mozdarani et al, 2005;Distel et al, 2006;Lisowska et al, 2006;Varga et al, 2006). The majority of data have been collected in studies considering breast cancer patients whose lymphocytes were irradiated in the G 2 phase of the cell cycle (Scott et al, 1994Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001;Buchholz and Wu, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005Howe et al, 2005;Djuzenova et al, 2006;Docherty et al, 2007). In a high number of these studies, it was found that approximately 40% of breast cancer patients show an increased G 2 chromosomal radiosensitivity (Scott et al, 1994Baria et al, 2001;Buchholz and Wu, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005.…”
mentioning
confidence: 99%
“…Our results indicate the indirect involvement of topoisomerase IIa in the formation of radiation-induced chromatid breaks from DSB, and suggest topoisomerase IIa as a possible factor in the inter-individual variation in chromatid radiosensitivity. British Journal of Cancer (2008) Human response to low doses of ionising radiation shows a wide variation as exemplified by the different frequencies of radiationinduced chromatid breaks observed in metaphase chromosomes in phytohaemagglutinin-stimulated peripheral blood T-lymphocytes (PBL) from different normal individuals and sporadic cancer cases, and elevated frequencies of such chromatid breaks have been linked to cancer susceptibility (Scott et al, 1994(Scott et al, , 1996Roberts et al, 1999;Baria et al, 2001Baria et al, , 2002Buchholz and Wu, 2001;Riches et al, 2001;Papworth et al, 2001;Smart et al, 2003;Baeyens et al, 2002Baeyens et al, , 2005. Using a short time interval (1-2 h) between radiation exposure and sampling, the metaphase cells (blocked with colcemid) collected are those that were in the G2-phase of the cell cycle at the time of exposure and show frequent chromatid breaks (discontinuities or terminal deletions) that have been shown to be induced as a linear function of radiation dose (Bryant, 1998).…”
mentioning
confidence: 99%